Globalization and the identity of the mental image structure of urban spaces - كمونة, أ.د.حيدر عبدالرزاق; خضير, د.عامر شاكر (Journal of Planner and Development, 2007)
This research discusses the subject of identity in the urban environment as it attempts to answer a number of questions that come with the concept of identity. The first of these questions: What is identity? Can a definition or conceptual framework be developed for identity? What about individual, collective, cultural, ethnic, political and regional identity? Is there a definition of identity in the urban environment in particular? If there is a definition of identity, what about social mobility responsible for social change? How can we see identity through this kinetics? Can we assume that identity in the urban environment has a variable structure or is of variable shape with a more stable structure? Can we determine the spatial-temporal path to change the shape and structure of urban identity in the urban environment?